Risks to human, animal, and environmental health caused by fireworks - Siqueira , Célia Gomes de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The production of fireworks is old, but it has modernized over time and has new uses. However, the activity has always brought many inconveniences, from simple to serious accidents that can lead to death, besides the environmental damage related to its use. This work carries out a descriptive research on the damage caused by fireworks to man, animals and the environment. The data collection was carried out in the Scopus, medRXiv, MEDLINE, SciELO and Google Scholar and Google Scholar databases. The results showed that, in addition to noise pollution, the use of fireworks is also associated with non-auditory health damage, such as irritation, cardiovascular disease, damage to cognitive ability and sleep disorders. Noise affects many species of amphibians, arthropods, fish, mammals, mollusks and reptiles, and can affect the reproductive cycle of birds. The use of fireworks, in addition to being related to respiratory diseases, due to air pollution, can cause behavioral reactions such as stress and anxiety in animals, and noise-induced panic. In some cases, with pets, just the use of sedatives solves the problem. The handling of fireworks is related to many accidents that mainly affect the upper limbs and the face, causing burns and even amputations, whose main victims are children. Despite all the problems related to fireworks, the authorities are flexible with their use, mainly because they are associated with festivities around the world and, consequently, directly linked to tourism. Intense and continuous preventive education work is necessary.